Peran Marketing Syariah dalam Penentu Penjualan Produk Farmasi di Wilayah Rayon V Klaten (Apotik Sumber Waras dan Apotik Yunmay Farma) - Budi, Dwi Setio (Journal of Economics Business Finance and Accounting, 2023)
This research aims to: 1) Describe the Islamic principles of sharia marketing in determining the sales of Pharmacy pharmaceutical products in the Klaten Rayon V Region, 2) Explain the advantages of Islamic principles of sharia marketing compared to conventional marketing in determining the sales of Pharmacy pharmaceutical products in the Klaten Rayon V Region, and 3) Knowing the obstacles to implementing Islamic principles of sharia marketing in determining sales of pharmacy pharmaceutical products in the Klaten Rayon V Region. This research is descriptive qualitative research. Researchers took locations in the Klaten rayon V area, including Delanggu, Juwiring, Wonosari, Polanharjo. Data collection techniques use interviews, observation and documentation. The validity of this research data uses triangulation of sources and methods. The analysis technique used is interactive model analysis. The results of this research show: 1) Islamic principles of sharia marketing in determining sales of pharmacy products in the Klaten District V Region using the Al-Qur'an and Hadith. 2) The advantages of Islamic principles of sharia marketing compared to conventional marketing in determining sales of pharmacy products in the Klaten Rayon V region include theistic (rabbaniyah), namely its religious nature (diniyyah); Ethical (akhlaqiyyah) which prioritizes moral issues (morals, ethics); Realism (al-waqi'yyah), is not an exclusive, fanatical, anti-modernity and rigid concept; Humanistic (al-insaniyyah) where human nature is maintained and maintained. 3) The obstacle to implementing Islamic principles of sharia marketing in determining sales of pharmacy products in the Klaten Rayon V region is the limited knowledge of pharmacists' sharia knowledge and drug sales.